Business Equity and Wealth Inequality in Central and Eastern Europe - Edison Jakurti (Comparative Economic Studies, 2024)
This paper analyzes the contribution of business equity, housing wealth and the rest of net wealth, to wealth inequality in eight post-socialist countries. Using the third wave of Household Finance and Consumption Survey, we decompose wealth inequality by factor components and use bootstrapping to provide statistical inference. We find that business equity, accounting for over 50% of within-country inequality in most cases, significantly surpasses the contribution of housing wealth. We extend our analysis through a novel simulation approach, employing counterfactual scenarios, to assess variations in between-country inequality. We find that the greatest reduction in the wealth inequality between these countries would occur if business equity were distributed more equally.
Keywords: G51; D31; D33; D63; P36; 330; Business equity; Wealth inequality; Factor decomposition; Simulation analysis; Central and Eastern Europe (CEE)